2022
DOI: 10.1016/j.jpra.2021.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of virtual assessment in hand trauma

Abstract: Summary A virtual clinic was developed from an existing telemedicine system to manage hand trauma in the Queen Victoria Hospital, East Grinstead, UK, during the first wave of the COVID-19 pandemic. This study evaluates the accuracy of the assessments made and makes comparisons to the traditional face-to-face clinic. The accuracy of assessment was analysed by comparing diagnosis with findings at surgery. One hundred and eighty-nine virtual assessments conducted by telephone with photograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…The authors found no difference between the three modalities, stating that telemedicine may represent a reliable alternative [ 39 ]. Similar results could be obtained by Westley et al [ 49 ] when comparing the accuracy of virtual versus face-to-face assessment in hand trauma: there were no significant differences [ 49 ]. Another important issue is patient satisfaction, as it is crucial for compliance.…”
Section: Discussionsupporting
confidence: 87%
“…The authors found no difference between the three modalities, stating that telemedicine may represent a reliable alternative [ 39 ]. Similar results could be obtained by Westley et al [ 49 ] when comparing the accuracy of virtual versus face-to-face assessment in hand trauma: there were no significant differences [ 49 ]. Another important issue is patient satisfaction, as it is crucial for compliance.…”
Section: Discussionsupporting
confidence: 87%
“… 45 Lastly, it must be acknowledged that our study did not include clinical samples, resulting in limited clinical applicability. 46 , 47 Further experiments will consider comparing the efficacy of the eschar preservation with other treatment methods in patients, aiming to provide more robust clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Atia et al [17] described checking up on patients less frequently, whereas most of authors used telemedicine to follow up with their patients [12,14,[22][23][24]. This is a method that proved its accuracy [25] and found satisfaction among patients [10,22,26], whereas surgeons had frequent issues [10,22]. The authors did not use telemedicine, and Toia et al [11] as well as Leti Acciaro et al [27] confirmed it might be an issue in Italy.…”
Section: Discussionmentioning
confidence: 99%